2009
DOI: 10.1007/s00535-008-2289-z
|View full text |Cite
|
Sign up to set email alerts
|

Impaired gastric motility and its relationship to reflux symptoms in patients with nonerosive gastroesophageal reflux disease

Abstract: Gastric hypomotility appears to be an important factor in reflux symptom generation in some NERD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 37 publications
(32 reference statements)
1
28
0
Order By: Relevance
“…All these clinical and basic data suggest the possibility that rikkunshito relieves the symptoms of PPI-refractory GERD patients, especially those with NERD, via attenuation of the motility dysfunction around the esophagogastric junction. On the basis of this consideration, some studies have been conducted to verify the usefulness of prokinetic agents such as mosapride, which promotes acetylcholine secretion via the stimulation of serotonin type 4 receptors, and itopride, which has antagonistic actions on dopamine D2 receptors, for PPI-refractory NERD patients [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…All these clinical and basic data suggest the possibility that rikkunshito relieves the symptoms of PPI-refractory GERD patients, especially those with NERD, via attenuation of the motility dysfunction around the esophagogastric junction. On the basis of this consideration, some studies have been conducted to verify the usefulness of prokinetic agents such as mosapride, which promotes acetylcholine secretion via the stimulation of serotonin type 4 receptors, and itopride, which has antagonistic actions on dopamine D2 receptors, for PPI-refractory NERD patients [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism is that gastric emptying is delayed, and dyspepsia is common in diabetic patients [43]. Gastric hypomotility appears to be an important factor in reflux symptom generation, thereby leading to Barrett's esophagus and adenocarcinoma [44]. Furthermore, most of diabetic individuals were overweight or obese.…”
Section: Discussionmentioning
confidence: 99%
“…If there is an interaction between delayed gastric emptying and GERD symptoms, prokinetic agents may improve GERD symptoms by resolving delayed gastric emptying. Kamiya et al [26] reported that the symptoms response rates to treatment with mosapride is higher in nonerosive reflux disease (NERD) patients with delayed gastric emptying than in NERD patients with normal gastric emptying. Their result is compatible with our present study.…”
Section: Discussionmentioning
confidence: 99%